Why the power of technology rarely goes to the people a new book reviewing 1,000 years of technological progress reveals how it benefits entrenched interests - Acemoglu, Daron; Johnson, Simon 1963-; Viswanath, Kaushik (MIT Sloan Management Review, 2023)
Throughout history, the advantages and costs of technological innovations have been unevenly distributed between the powerful and the rest of society, assert economists Daron Acemoglu and Simon Johnson in their new book, Power and Progress: Our Thousand-Year Struggle Over Technology and Prosperity. In a Q&A, they discuss what's wrong with today's approach to automation, why machine usefulness is more important than machine intelligence, and what techno-optimists and -pessimists both get wrong.